Kepemimpinan Kepala Desa Dalam Meningkatkan Efektivitas Kinerja Perangkat Desa: (Studi Deskriptif analisis di Desa Jayasari Kecamatan Langkaplancar Kabupaten Pangandaran) - Riza Purnama; Tina Cahya Mulyatin; Rakhmat Saleh (Jurnal Ilmu Pemerintahan, 2024)
The results of the initial exploration found that the leadership of the Village Head was not optimal in improving the effectiveness of the performance of village officials. The objectives of this study are as follows: to determine the leadership of the Village Head in improving the effectiveness of the performance of village officials. The method used in this research is descriptive analysis.based on the results of the study it is known that: 1) The leadership of the Village Head has not been optimal in improving the effectiveness of the performance of village officials in accordance with the characteristics of good leadership according to Pasolong (2015: 46). This is because in carrying out his leadership to the village has not been able to increase the active role of employees in participating in village deliberations, besides that the village head has difficulty in choosing alternatives to an activity, the level of cooperation between village officials is still lacking. 2) There are obstacles to the Village Head in carrying out his leadership to improve the effectiveness of the performance of village officials. This is because the village head is not supported by the active role of village officials in participating in village meetings, besides that the village head has difficulty in choosing alternatives to an activity, lack of cooperation between village officials, besides the lack of conformity of the performance of village officials with what is expected by the village head.